An Exploratory Study Into the Negotiation of Cyber-Security Within the Family Home - Muir, Kate; Joinson, Adam (Frontiers in Psychology, 2020)
Given the increasingly young age that children are using technology and accessing the internet and its associated risks, it is important we understand how families manage and negotiate cyber-security within the home. We conducted an exploratory qualitative study with thirteen families (fourteen parents and nineteen children) in the south-west of the UK about their main cyber-security concerns and management strategies. Thematic analysis of the results revealed that families were concerned about cyberbullying, online stranger danger, privacy, content, financial scams and technical threats. Both parents and children drew on family, friends and trusted others as resources, and used a variety of strategies to manage these threats including rules and boundaries around technology, using protective functions of technology, communication and education around safety. There were tensions between parents and children over boundaries, potentially putting families at risk if children break household rules around cyber-security. Finally, parents expressed the feeling they were in a ‘whole new world’ of cyber-security threats, and that positive and negative aspects of technology must be constantly balanced. However, parents also felt that the challenges in managing family security are the same ones that have always faced parents – it is just that the context is now digital as well as physical.